Enhancing Aviation Safety: The Role of Mentorship and Coaching in Developing Skilled Pilots and Ground Crew - Rini Sadiatmi; Catra Indra Cahyadi; Inda Tri Pasa; Fauziah Nur; Eko Risdianto; Fadillah Eka Nuranisa (Smart Society, 2025)
Aviation safety is heavily influenced by the quality of human resources, particularly pilots and ground crew. Although technology has advanced significantly, human error remains the primary cause of aviation accidents; therefore, strengthening both technical and non-technical competencies through effective human resource development strategies is essential. This study aims to explore the role of mentorship and coaching in improving aviation safety by enhancing the technical and non-technical skills of pilots and ground crew. The study employed a systematic literature review (SLR) approach based on PRISMA guidelines. Of the 194 studies initially identified, 34 articles met the inclusion criteria and were analyzed in depth using VOSviewer and Biblioshiny for thematic mapping and bibliometric visualization. The findings indicate that mentorship is effective in fostering a culture of safety, confidence, and professionalism, while coaching enhances technical performance through structured feedback and simulation-based approaches. Approximately 35% of the reviewed studies reported improvements in non-technical skills, while 26% demonstrated positive impacts on safety outcomes. The integration of mentorship and coaching forms a holistic competency framework that positively influences operational safety. This study concludes that mentorship and coaching are strategic instruments for enhancing aviation safety and should be systematically integrated into formal aviation training programs. This research contributes to the aviation safety literature by synthesizing evidence-based mentorship and coaching practices and providing practical guidance for developing integrated human resource development frameworks within the aviation industry.